Comparison of two automated periodontal probes and two probes with a conventional readout in periodontal maintenance patients - D. S. Barendregt (journal of clinical periodontology, 2006)
Aim: The aim of the present study was to test in periodontal maintenance patients whether the systems for pressure control that have been commercially developed contribute to more reproducible probing depth measurements as compared with a manual probe. Material and Methods: In 12 patients duplicate measurements were made at day 0 and 1 week later. In each patient four teeth with the deepest pockets were measured at six sites. In total 288 sites were available for comparisons. The Florida Probe s (FP) (159 N/cm2), the Jonker Probe s (JP) (153 N/cm2), the Brodontic s probe (BP) (255 N/ cm2) and the manual probe (MP) were used in a randomized scheme. Results: Mean probing measurements showed for the FP and the JP lower recordings than for the BP and manual probe. The FP, the BP and the MP showed no differences between the duplicate measurements, except for the JP where the second measurement was deeper. Correlation coefficients between measurements at day 0 and 1 week show for the BP and the MP are 0.90 and 0.89, respectively, while for the FP and the JP they are 0.76 and 0.75, respectively. Conclusion: The BP and the MP appear to be reliable tools for reproducible pocket depth measurements in periodontal maintenance patients.